Positive electrode active material, preparation method thereof, positive electrode including the positive electrode active material, and lithium secondary battery

A lithium nickel-manganese-aluminum composite oxide with an aluminum and yttrium coating addresses the scarcity of cobalt by enhancing structural stability and reducing gas generation, ensuring high capacity and long life in lithium secondary batteries.

JP2024178143AActive Publication Date: 2024-12-24SAMSUNG SDI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024094857
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-06-12
Publication Date
2024-12-24
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The increasing demand for large-sized, high-capacity, and high-energy-density lithium secondary batteries has highlighted the scarcity and high cost of cobalt, necessitating the development of cobalt-free or low-cobalt positive electrode active materials that maintain high capacity, structural stability, and long life characteristics, especially under high voltage and high temperature conditions.

Method used

A positive electrode active material comprising a lithium nickel-manganese-aluminum composite oxide core particle with a coating layer containing aluminum and yttrium, where nickel content is 60 mol% or more, aluminum content is 0.1-2 mol%, and yttrium content is 0.05-1 mol%, forming a uniform coating layer to enhance structural stability and reduce side reactions.

Benefits of technology

The material minimizes production costs, maximizes capacity, and ensures long life characteristics with reduced gas generation under high voltage and high temperature conditions, improving high voltage characteristics and maintaining efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178143000001_ABST
    Figure 2024178143000001_ABST
Patent Text Reader

Abstract

To provide: a positive electrode active material including a lithium nickel-manganese-aluminum-based composite oxide, which is ensured in economy, high capacity and long life characteristics, and is also improved in high voltage characteristics and high temperature characteristics; a preparation method thereof; a positive electrode including the positive electrode active material; and a lithium secondary battery.SOLUTION: The present invention relates to a positive electrode active material, a preparation method thereof, a positive electrode including the positive electrode active material, and a lithium secondary battery. The positive electrode active material includes a core particle containing a lithium nickel-manganese-aluminum-based composite oxide, and a coating layer disposed on a surface of the core particle and containing aluminum and yttrium. A nickel content is greater than or equal to 60 mol% based on 100 mol% of a total metal excluding lithium, and an aluminum content of the coating layer is 0.1 mol% to 2 mol%, and a yttrium content of the coating layer is 0.05 mol% to 1 mol%, each based on 100 mol% of the total metal excluding lithium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a method for producing the same, a positive electrode containing the same, and a lithium secondary battery. [Background technology]

[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.

[0003] In order to realize lithium secondary batteries that meet these applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, in recent years, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has rapidly increased, the supply of positive electrode active materials containing the rare metal cobalt is expected to be extremely short. In other words, since cobalt is expensive and there are not many remaining reserves, it is necessary to develop positive electrode active materials that do not contain cobalt or have a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese-aluminum composite oxide, which ensures economical efficiency, high capacity, and long life characteristics, and has improved high voltage characteristics and high temperature characteristics, a method for producing the same, and a positive electrode and a lithium secondary battery containing the same. [Means for solving the problem]

[0005] In one embodiment of the present invention, there is provided a positive electrode active material comprising core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer located on the surface of the core particles and containing aluminum and yttrium, wherein the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, the aluminum content of the coating layer is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium, and the yttrium content of the coating layer is 0.05 mol % to 1 mol %.

[0006] In another embodiment of the present invention, there is provided a method for producing a positive electrode active material, comprising: mixing a nickel-manganese-aluminum-based composite hydroxide and a lithium raw material; performing a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide; introducing the obtained lithium nickel-manganese-aluminum-based composite oxide into a solution obtained by mixing an aluminum raw material and an yttrium raw material in an aqueous solvent; mixing the resulting solution; drying the resulting solution; and performing a second heat treatment to obtain a positive electrode active material, wherein the nickel content in the nickel-manganese-aluminum-based composite hydroxide is 60 mol % or more relative to 100 mol % of all metals, excluding lithium, the aluminum content in the aluminum raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals, excluding lithium, in the positive electrode active material. The yttrium content in the yttrium raw material is 0.05 mol % to 1 mol % relative to 100 mol % of all metals, excluding lithium, in the positive electrode active material.

[0007] In yet another embodiment of the present invention, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.

[0008] In yet another embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention

[0009] The positive electrode active material according to an embodiment of the present invention minimizes production costs and maximizes capacity, while ensuring long life characteristics and improving high voltage and high temperature characteristics. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage driving conditions, realize long life characteristics, and effectively suppress gas generation problems caused by high voltage and high temperature driving. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a scanning electron microscopy (SEM) image of the positive electrode active material of Comparative Example 1. [Diagram 3] 1 is a scanning electron microscopy (SEM) image of the positive electrode active material of Comparative Example 1. [Figure 4] 1 is a SEM image of the positive electrode active material of Comparative Example 2. [Diagram 5] 1 is a SEM image of the positive electrode active material of Comparative Example 2. [Figure 6] 1 is a SEM image of the positive electrode active material of Example 2. [Figure 7] 1 is a SEM image of the positive electrode active material of Example 2. [Figure 8] 1 shows the results of SEM-EDS analysis of the positive electrode active material of Example 2. [Figure 9] 1 shows the results of SEM-EDS analysis of the positive electrode active material of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.

[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0015] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0016] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0017] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size can be obtained by measuring using a dynamic light scattering method, counting the number of particles for each particle size range by performing data analysis, and then calculating the average particle size value. Unless otherwise defined, the average particle size means the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution. In addition, unless otherwise defined, the average particle size can be obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly from a scanning electron microscope image to obtain a particle size distribution, and taking the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution as the average particle size.

[0018] As used herein, "or" is not to be construed in an exclusive sense, e.g., "A or B" is to be construed as including A, B, A+B, etc.

[0019] The term "metal" is interpreted as including general metals, transition metals, and metalloids (semimetals).

[0020] positive electrode active material In one embodiment of the present invention, there is provided a positive electrode active material comprising core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer located on the surface of the core particles and containing aluminum and yttrium, wherein the nickel content is 60 mol % or more relative to 100 mol % of all metals excluding lithium, the aluminum content of the coating layer is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium, and the yttrium content of the coating layer is 0.05 mol % to 1 mol %.

[0021] In recent years, the price of cobalt, a rare metal, has been soaring, and there is a demand for the development of positive electrode active materials that do not contain cobalt or that have a reduced cobalt content. Among these, positive electrode active materials with an olivine crystal structure, such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or a spinel crystal structure, such as lithium manganese oxide (LMO), have limitations in achieving high capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have excellent capacity and efficiency characteristics because they can increase the lithium content within the structure, making them suitable as materials for high-capacity batteries. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.

[0022] In one embodiment, aluminum is introduced as a base material and a lithium nickel-manganese-aluminum composite oxide is applied to the core particles to improve structural stability and minimize production costs. In addition, aluminum and yttrium are simultaneously coated at specific contents to form a uniform coating layer, thereby maximizing capacity and efficiency, and reducing the amount of gas generation even under high voltage and high temperature conditions, thereby providing a positive electrode active material that can achieve long life characteristics.

[0023] Core Particles The core particles contain a lithium nickel-manganese-aluminum composite oxide.

[0024] The nickel content is 60 mol% or more relative to 100 mol% of all metals excluding lithium in the positive electrode active material. Nickel is contained in the core particles, but a part of it can migrate to the coating layer during the coating process, and therefore the nickel content means the nickel content contained in the entire positive electrode active material. The nickel content can be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol% relative to 100 mol% of all metals excluding lithium in the positive electrode active material. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0025] The manganese content is, for example, 10 mol% to 39 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. Manganese is contained in the core particles, but a part of it can move to the coating layer during the coating process, so the manganese content means the manganese content contained in the entire positive electrode active material. When the manganese content satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.

[0026] The aluminum content in the core particle is 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol% based on 100 mol% of all metals except lithium in the positive electrode active material. Here, the aluminum content means the content of aluminum present in the core particle. When the aluminum content of the core particle satisfies the above range, even if the cobalt in the core particle is removed, a stable layered structure can be maintained, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.

[0027] According to one embodiment, the concentration of aluminum may be uniform within the core particle. That is, aluminum may have a concentration gradient from the center to the surface within the core particle, or the aluminum concentration in the outside of the core particle is not higher or lower than in the inside of the core particle, and aluminum may be uniformly dispersed within the core particle. This may be a structure obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without further doping aluminum in the synthesis process of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content within the primary particle may be similar or the same regardless of the position of the primary particle. That is, when a primary particle is selected from an arbitrary position in the cross section of the secondary particle and the aluminum content is measured within the primary particle, not at the interface of the primary particle, the aluminum content may be the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or close to the surface of the secondary particle. In such a structure, even if cobalt is absent or present in only a very small amount, a stable layered structure can be maintained, no aluminum by-products or aluminum agglomerates are generated, and the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.

[0028] The lithium nickel-manganese-aluminum composite oxide is represented, for example, by the following chemical formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0029] In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01≦z1≦0.03, 0≦w1≦0.29, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

[0030] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2 may hold. Also, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79, 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3, 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019, 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09 and the like may hold.

[0031] The lithium nickel - manganese - aluminum - based composite oxide of the core particles can be, for example, a cobalt - free compound that does not contain cobalt or contains an extremely small amount of cobalt.

[0032] The core particles can be in the form of secondary particles formed by aggregation of a plurality of primary particles. The secondary particles can be spherical, ellipsoidal, polyhedral, or irregular in shape, and the primary particles can be spherical, ellipsoidal, plate - shaped, or a combination thereof.

[0033] The core particles are liable to be chemically attacked by components in the electrolyte during battery driving under high - voltage or high - temperature conditions, and many side reactions with the electrolyte can occur. As a result, there are problems such as a large amount of gas generation and a decrease in battery life and safety. However, by introducing a coating layer according to an embodiment described later, such problems can be solved.

[0034] Coating Layer The aluminum content in the coating layer is characterized by being 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer, apart from the aluminum contained in the core particles. The aluminum content in the coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the aluminum content of the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effect of suppressing side reactions with the electrolyte.

[0035] The yttrium content in the coating layer is 0.05 mol% to 1 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.1 mol% to 1 mol%, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, or 0.1 mol% to 0.6 mol%. When the yttrium content satisfies the above range, the positive electrode active material forms a good coating layer without a decrease in capacity or an increase in resistance, effectively suppressing side reactions with the electrolyte and effectively reducing the amount of gas generation under high voltage or high temperature conditions.

[0036] In one embodiment, both aluminum and yttrium are contained in the coating layer, and compared to a case in which only one of the two is contained, the amount of gas generated under high voltage or high temperature operating conditions can be significantly reduced, thereby improving the life characteristics.

[0037] According to an embodiment, the coating layer may be in the form of a film that continuously surrounds the surface of the core particle, for example, in the form of a shell that surrounds the entire surface of the core particle. This is distinguished from a structure in which only a part of the surface of the core particle is partially coated. According to an embodiment, the coating layer may be formed in a form that entirely surrounds the surface of the core particle, but may be formed with a very thin and uniform thickness, so that the positive electrode active material does not increase in resistance or decrease in capacity, improves structural stability, effectively suppresses side reactions with the electrolyte, reduces the amount of gas generation under high voltage and high temperature conditions, and achieves long life characteristics.

[0038] The thickness of the coating layer is 30 nm to 500 nm, and may be, for example, 30 nm to 450 nm, 30 nm to 400 nm, 30 nm to 350 nm, 30 nm to 300 nm, 30 nm to 250 nm, 30 nm to 200 nm, 30 nm to 150 nm, 50 nm to 500 nm, 80 nm to 500 nm, or 100 nm to 500 nm. When the coating layer satisfies the above thickness range, the coating can improve the structural stability of the positive electrode active material and effectively suppress side reactions with the electrolyte, even if the coating does not increase the resistance or decrease the capacity. The thickness of the coating layer can be measured, for example, by TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0039] According to an embodiment, the coating layer has a thickness of tens to hundreds of nanometers and is uniform. For example, the deviation of the coating layer thickness within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation of the coating layer thickness refers to the thickness of the coating layer within one positive electrode active material particle. The deviation of the coating layer thickness means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average value is divided by the arithmetic average value and multiplied by 100. The deviation of the coating layer thickness satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0040] In terms of the properties of each element in the coating layer, aluminum may exist in the form of a continuous film, and yttrium may exist in the form of islands.

[0041] In one embodiment, aluminum and yttrium may be mixed in one coating layer, and in this case, aluminum may be present in the form of a continuous film and yttrium may be present in the form of islands, but the forms are not limited thereto.

[0042] In another embodiment, aluminum and yttrium may form separate layers. For example, the positive electrode active material according to an embodiment may include a first coating layer containing aluminum located on the surface of the core particle, and a second coating layer containing yttrium located on the first coating layer. Aluminum is first attached or absorbed on the surface of the core particle to form a first coating layer in the form of a thin film, and then yttrium is coated on the first coating layer to form a second coating layer. Of course, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an aluminum-rich coating layer mainly composed of aluminum, and the second coating layer may be an yttrium-rich coating layer mainly composed of yttrium. In this case, yttrium may be present in the second coating layer in the form of islands, but is not particularly limited.

[0043] The thickness of the first coating layer and the second coating layer is not particularly limited, but the thickness of the first coating layer is 10 nm to 200 nm, for example, 20 nm to 200 nm, 30 nm to 200 nm, or 30 nm to 180 nm. The thickness of the second coating layer is 20 nm to 300 nm, for example, 20 nm to 250 nm, 20 nm to 200 nm, 30 nm to 300 nm, or 50 nm to 300 nm. When each thickness satisfies the above range, the coating can improve the structural stability of the positive electrode active material without increasing the resistance or decreasing the capacity, and can effectively suppress side reactions with the electrolyte to effectively reduce the amount of gas generated during high voltage and high temperature operation.

[0044] Meanwhile, the coating layer may further contain nickel, manganese, or a combination thereof in addition to aluminum and yttrium. Nickel and manganese are contained in the core particles and flow in during the coating layer formation process, and the content thereof is not particularly limited. The coating layer according to an embodiment necessarily contains aluminum and yttrium, and selectively contains nickel and manganese, and is formed with a thin and uniform thickness, which can improve the high voltage characteristics and life characteristics of the positive electrode active material.

[0045] Grain boundary coating part In the process of forming the coating layer, aluminum may be diffused into the core particles. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum located on the surface of the primary particle inside the secondary particle. Here, the secondary particle refers to the core particle, and the inside of the secondary particle refers to the entire inside except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the core particle, and refers to a coating portion formed on the surface of the primary particle located inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming the aluminum grain boundary coating portion, the positive electrode active material is structurally more stabilized and the life characteristics are improved.

[0046] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.

[0047] In addition, the grain boundary coating portion may further include nickel, manganese, yttrium, or a combination thereof in addition to aluminum.

[0048] The average particle size (D 50The average particle size is determined by measuring the size (diameter or major axis length) of 20 or more particles randomly in a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and calculating the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution. 50 When the average particle size of the positive electrode active material satisfies the above range, high capacity and long life can be achieved, and it is advantageous to form the coating layer according to an embodiment.

[0049] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.

[0050] In addition, the positive electrode active material according to an embodiment may be characterized in that it does not contain sodium. Although sodium ions can be generally used in a process for manufacturing a positive electrode active material, according to a manufacturing method described below, it is possible to form core particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.

[0051] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material is provided, which includes mixing a nickel-manganese-aluminum-based composite hydroxide and a lithium raw material, performing a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide, introducing the obtained lithium nickel-manganese-aluminum-based composite oxide into a solution obtained by mixing an aluminum raw material and an yttrium raw material in an aqueous solvent, mixing the resulting mixture, drying the mixture, and performing a second heat treatment to obtain a positive electrode active material. Here, the nickel content in the nickel-manganese-aluminum-based composite hydroxide is 60 mol% or more relative to 100 mol% of the total metals in the positive electrode active material, the aluminum content in the aluminum raw material is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals in the positive electrode active material excluding lithium, and the yttrium content in the yttrium raw material is 0.05 mol% to 1 mol% relative to 100 mol% of the total metals in the positive electrode active material excluding lithium. The above-mentioned positive electrode active material can be produced by the above method.

[0052] The nickel-manganese-aluminum composite hydroxide is a precursor of core particles, and may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, and may contain no cobalt or a very small amount of cobalt, for example, a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese-aluminum composite hydroxide may be prepared by a conventional coprecipitation method.

[0053] A method for producing a positive electrode active material according to an embodiment is characterized in that, when producing core particles, aluminum is not further doped, and instead, an aluminum raw material is used when producing a precursor, thereby using a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed within the structure as a precursor. By using such a precursor, a positive electrode active material that does not contain cobalt and that stably maintains a layered structure even after repeated charging and discharging can be produced, and aluminum by-products and aluminum aggregates are not formed, thereby improving the capacity, efficiency characteristics, and life characteristics of the positive electrode active material.

[0054] The nickel content in the nickel-manganese-aluminum composite hydroxide is 60 mol% or more relative to 100 mol% of the total metal, and can be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0055] The manganese content in the nickel-manganese-aluminum composite hydroxide is 10 mol% to 39 mol% relative to 100 mol% of the total metal, and may be 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. Also, the aluminum content in the nickel-manganese-aluminum composite hydroxide is 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more relative to 100 mol% of the total metal, and may be, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the manganese and aluminum contents in the composite hydroxide satisfy the above ranges, respectively, high capacity can be realized and the structural safety of the positive electrode active material can be improved, and the production price can be reduced to improve the economic efficiency.

[0056] In the nickel-manganese-aluminum composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such nickel-manganese-aluminum composite hydroxide is economical as it can avoid the increase in unit price due to cobalt, and can maximize capacity and improve structural stability.

[0057] An example of the nickel-manganese-aluminum composite hydroxide is represented by the following chemical formula 2. [Chemical formula 2] Ni x2 Mn y2 Al z2 M 2w2 (OH)2

[0058] In the chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, 0≦w2≦0.29, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr.

[0059] The nickel-manganese-aluminum composite hydroxide is in the form of particles, and the average particle size (D 50 ) can be 10 μm to 18 μm, 11 μm to 16 μm, or 12 μm to 15 μm.

[0060] The nickel-manganese-aluminum composite hydroxide and the lithium raw material can be mixed at a molar ratio of 1:0.9 to 1:1.8, for example, at a molar ratio of 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2.

[0061] The first heat treatment can be carried out in an oxygen atmosphere, for example, at a temperature range of 750° C. to 950° C., or 780° C. to 900° C., or 810° C. to 890° C., for 2 hours to 20 hours, or 4 hours to 12 hours.

[0062] The first heat treatment can produce a lithium nickel-manganese-aluminum composite oxide. The obtained composite oxide contains nickel at 60 mol % or more, for example, 60 mol % to 80 mol %, based on 100 mol % of the total metal, and does not contain cobalt or can contain a very small amount of cobalt of 0.01 mol % or less. Such composite oxides have a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxides and lithium nickel-cobalt-aluminum composite oxides, and many surface properties are different, so that it is impossible to form a good coating layer with a uniform film shape by using existing coating methods. In one embodiment, a method is provided for improving high voltage and high temperature properties by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese-aluminum composite oxide having a very small amount of cobalt and a nickel content of 60 mol % or more.

[0063] In one embodiment, the lithium nickel-manganese-aluminum based composite oxide obtained by the first heat treatment is mixed in an aqueous solvent containing an aluminum raw material and an yttrium raw material, and then dried and subjected to a second heat treatment to form a coating layer according to one embodiment. This may be a type of wet coating method.

[0064] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, which is advantageous in forming a coating layer having a uniform thickness on the surface of the lithium nickel-manganese-aluminum composite oxide particles. The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof.

[0065] The aluminum raw material is a raw material for forming a coating layer, and the aluminum content in the aluminum raw material can be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metal excluding lithium in the finally obtained positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. Similarly, the yttrium raw material is a raw material for forming a coating layer, and the yttrium content in the yttrium raw material can be designed to be 0.05 mol% to 1 mol% with respect to 100 mol% of the total metal excluding lithium in the finally obtained positive electrode active material, for example, 0.1 mol% to 1 mol%, 0.1 mol% to 0.9 mol%, 0.1 mol% to 0.8 mol%, or 0.1 mol% to 0.6 mol%. By designing the content of the coating material within the above range, a coating layer having a uniform thickness of tens to hundreds of nanometers can be formed, reducing the amount of gas generation in the lithium secondary battery under high voltage or high temperature operating conditions, and improving the high capacity and long life characteristics.

[0066] The solution in which the aluminum raw material and the yttrium raw material are mixed in an aqueous solvent has a pH of 1.5 to 3.5, and can be, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese-aluminum composite oxide can be added to the aqueous solvent in which the aluminum raw material and the yttrium raw material are mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring is 4.5 to 8.5, and can be, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.

[0067] Drying after the mixing step can be understood as a step of removing the solvent, and can be carried out at, for example, 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C.

[0068] The second heat treatment can be understood as a process for forming a coating layer, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time is preferably the same as or shorter than the first heat treatment time. By carrying out the second heat treatment under such conditions, a desired coating layer can be obtained.

[0069] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive material, or a combination thereof.

[0070] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2 ~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.3 g / cc to 3.7 g / cc, for example, 3.3 g / cc to 3.6 g / cc or 3.4 g / cc to 3.58 g / cc. When the positive electrode active material according to an embodiment is applied, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the above-mentioned ranges of loading level and positive electrode density is suitable for realizing a lithium secondary battery with high capacity and high energy density.

[0071] binder The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.

[0072] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause a chemical change in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0073] The content of the binder and the conductive material may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.

[0074] The positive electrode current collector can be made of Al, but is not limited to this.

[0075] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.

[0076] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, etc. types according to their shapes. FIG. 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG. 1, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0077] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long life characteristics.

[0078] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive material, or a combination thereof.

[0079] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of being doped and dedoped with lithium, or a transition metal oxide.

[0080] As the substance capable of reversibly inserting / desorbing the lithium ions, a carbon-based negative electrode active material can be used, which can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0081] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0082] As the substance capable of doping and dedoping lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiOx (0 < x ≤ 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, an Sn alloy, or a combination thereof.

[0083] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D of the silicon-carbon composite particles 50) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.

[0084] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0085] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, relative to 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, relative to 100% by weight of the silicon-carbon composite.

[0086] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50 The diameter of the silicon particles may be from 10 nm to 1 μm, or from 10 nm to 200 nm. The silicon particles may be present as silicon alone, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon is SiO xIt can be represented by (0 < x ≤ 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.

[0087] The Si-based negative electrode active material or Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are used in combination, the mixing ratio can be 1:99 to 90:10 by weight.

[0088] binder The binder plays a role of making the negative electrode active material particles adhere well to each other and making the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.

[0089] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0090] The aqueous binder can be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0091] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.

[0092] The dry binder can be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0093] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and may be any material that does not cause chemical changes in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0094] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.

[0095] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.

[0096] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.

[0097] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.

[0098] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.

[0099] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, the mixing ratio may be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0100] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.

[0101] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0102] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.

[0103] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0104] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0105] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.

[0106] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a two-layer separator of polyethylene / polypropylene, a three-layer separator of polyethylene / polypropylene / polyethylene, or a three-layer separator of polypropylene / polyethylene / polypropylene.

[0107] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0108] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0109] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.

[0110] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from (meth)acrylamide, a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a second structural unit including at least one of a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.

[0111] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.

[0112] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0113] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.

[0114] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0115] Example 1 1. Manufacturing of positive electrode active material Ni 0.75 Mn 0.24 Al 0.01 (OH)2 and LiOH were mixed in a molar ratio of 1:1 and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a compound with the composition LiNi 0.75 Mn 0.24 Al0.01 O2 and the average particle size (D 50 A composite oxide in the form of secondary particles having a particle size of about 14 μm was produced.

[0116] Aluminum sulfate and yttrium nitrate were mixed in a distilled water solvent, and then the composite oxide prepared was added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% relative to 100 mol% of the total metals excluding lithium in the final positive electrode active material, and the aluminum content in the yttrium nitrate was designed to be 1.0 mol% relative to 100 mol% of the total metals excluding lithium in the final positive electrode active material. The solvent was removed from the mixed solution, which was then dried at 190°C, and a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to prepare the final positive electrode active material.

[0117] 2. Manufacturing of lithium secondary batteries 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm. 2 and the density of the final rolled cathode was about 3.4 g / cc.

[0118] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.

[0119] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte solution prepared by dissolving 1M LiPF6 in a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0120] Example 2 In the preparation of the positive electrode active material, the yttrium content in the yttrium nitrate was designed to be 0.2 mol% based on 100 mol% of the total metals excluding lithium in the final positive electrode active material, and mixed. The positive electrode active material and the lithium secondary battery were prepared in substantially the same manner as in Example 1.

[0121] Example 3 In the preparation of the positive electrode active material, the yttrium content in the yttrium nitrate was designed to be 0.5 mol% based on 100 mol% of the total metals excluding lithium in the final positive electrode active material, and mixed. The positive electrode active material and the lithium secondary battery were prepared in substantially the same manner as in Example 1.

[0122] Comparative Example 1 In the manufacture of the positive electrode active material, the aluminum and yttrium coating process is not performed, and LiNi 0.75 Mn 0.24 Al 0.01 A positive electrode active material and a lithium secondary battery were produced in substantially the same manner as in Example 1, except that the O2 composite oxide itself was used as the positive electrode active material.

[0123] Comparative Example 2 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 1, except that in the preparation of the positive electrode active material, yttrium nitrate was not added to the distilled water solvent, but only aluminum sulfate and a composite oxide were added to perform aluminum coating.

[0124] Comparative Example 3 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 2, except that in the preparation of the positive electrode active material, aluminum sulfate was not added to the distilled water solvent, and only yttrium coating was performed by adding only yttrium nitrate and composite oxide.

[0125] Comparative Example 4 A positive electrode active material and a lithium secondary battery were manufactured in a manner substantially similar to that of Example 3, except that in the preparation of the positive electrode active material, aluminum sulfate was not added to the distilled water solvent, and only yttrium coating was performed by adding only yttrium nitrate and composite oxide.

[0126] For ease of understanding, the coating designs of the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 4 are simply shown in Table 1 below.

[0127] Evaluation example 1: Analysis of the surface of the positive electrode active material The positive electrode active materials prepared in Example 2, Comparative Example 1, and Comparative Example 2 were photographed by a scanning electron microscope and compared. Figures 2 and 3 are SEM images of the particle surface of the positive electrode active material of Comparative Example 1, which was not coated, Figures 4 and 5 are SEM images of the particle surface of the positive electrode active material of Comparative Example 2, which was only aluminum coated, and Figures 6 and 7 are SEM images of the particle surface of the positive electrode active material of Example 2. Referring to Figures 2 to 7, it was confirmed that the positive electrode active material of Example 2 had a different surface shape from Comparative Examples 1 and 2.

[0128] 8 and 9 show SEM-EDS analysis images of a cross section of the positive active material prepared in Example 2. Referring to Fig. 8 and Fig. 9, it was confirmed that a coating layer containing Al and Y was uniformly formed on the surface of the positive active material of Example 2.

[0129] Evaluation example 2: Initial charge / discharge capacity and efficiency evaluation The lithium secondary batteries manufactured in Examples 1 to 3 and Comparative Examples 1 to 4 were initially charged and discharged at a constant current of 0.2 C at 25° C. up to an upper limit voltage of 4.45 V, and at a constant voltage of 0.05 C, and then discharged at 0.2 C down to a cut-off voltage of 3.0 V. Table 1 below shows the initial charge capacity, initial discharge capacity, and the ratio of the latter to the former, which have been efficiently calculated.

[0130] Evaluation example 3: High temperature life characteristics Following the initial charge and discharge of Evaluation Example 1, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V at 45° C. was repeated 50 or more times, and the ratio of the 50 cycle discharge capacity to the initial discharge capacity was calculated, as shown in Table 1 below.

[0131] Evaluation example 4 :Evaluation of gas generation rate The batteries of Examples 1 to 3 and Comparative Examples 1 to 4 were initially charged to 4.45 V as in Evaluation Example 1, and then stored at 90° C. for 4 hours, after which the amount of gas generated in the batteries was measured. The results are shown in Table 1 below.

[0132] [Table 1]

[0133] Referring to Table 1, it can be seen that the lithium secondary batteries of Examples 1 to 3 achieved charge / discharge capacity and efficiency characteristics at levels higher or equal to those of the Comparative Examples, while improving high-temperature life characteristics and reducing the amount of gas generation under high voltage and high temperature conditions. Comparative Example 1, in which no coating was performed, had poor high-temperature life characteristics and a high amount of gas generation, while Comparative Example 2, in which only an aluminum coating was performed, and Comparative Example 4, in which only an yttrium coating was performed, showed a higher amount of gas generation under high voltage and high temperature conditions than the Examples.

[0134] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]

[0135] 100 Lithium secondary battery 10 positive electrode 20 negative electrode 30 Separator 40 Electrode assembly 50 cases

Claims

1. Core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer located on a surface of the core particle and containing aluminum and yttrium; The nickel content is 60 mol % or more based on 100 mol % of all metals excluding lithium, The aluminum content of the coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium; The coating layer has an yttrium content of 0.05 mol % to 1 mol %.

2. 2. The positive electrode active material according to claim 1, wherein the aluminum content of the coating layer is 0.5 mol% to 1.5 mol% and the yttrium content of the coating layer is 0.1 mol% to 0.8 mol% relative to 100 mol% of all metals excluding lithium.

3. The positive electrode active material according to claim 1 , wherein the coating layer is in the form of a shell that continuously surrounds the surface of the core particle.

4. The positive electrode active material according to claim 1 , wherein the coating layer has a thickness of 30 nm to 500 nm.

5. The positive electrode active material of claim 1 , wherein the coating layer has a thickness deviation of 20% or less within one positive electrode active material.

6. 2. The positive electrode active material according to claim 1, wherein in the coating layer, aluminum is present in the form of a continuous film and yttrium is present in the form of islands.

7. The positive electrode active material according to claim 1 , wherein aluminum and yttrium are mixed in the coating layer.

8. 2. The positive electrode active material of claim 1, comprising: a first coating layer located on a surface of the core particle and containing aluminum; and a second coating layer located on the first coating layer and containing yttrium.

9. The thickness of the first coating layer is between 10 nm and 200 nm; The cathode active material according to claim 8, wherein the second coating layer has a thickness of 20 nm to 300 nm.

10. The positive electrode active material of claim 1 , wherein the coating layer further contains nickel, manganese, or a combination thereof.

11. 2. The positive electrode active material according to claim 1, wherein the content of nickel is 60 mol % to 80 mol % relative to 100 mol % of all metals excluding lithium.

12. 2. The positive electrode active material according to claim 1, wherein the content of aluminum in the core particles is 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.

13. The lithium nickel-manganese-aluminum composite oxide of the core particle is represented by chemical formula 1, [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01≦z1≦0.03, 0≦w1≦0.29, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

14. 2. The positive electrode active material according to claim 1, wherein the content of cobalt is 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.

15. 2. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese-aluminum based composite oxide of the core is a cobalt-free compound.

16. The positive electrode active material according to claim 1 , wherein the core particle is in the form of a secondary particle formed by agglomeration of a plurality of primary particles.

17. The positive electrode active material of claim 16 , further comprising a grain boundary coating portion located on a surface of the primary particle inside the secondary particle and containing aluminum.

18. The positive electrode active material of claim 17 , wherein the grain boundary coating further contains nickel, manganese, yttrium, or a combination thereof.

19. The positive electrode active material according to claim 17 , wherein the content of aluminum in the grain boundary coating portion is less than the content of aluminum in the coating layer.

20. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the average particle diameter is 10 μm to 18 μm.

21. The cathode active material of claim 1 , wherein the cathode active material does not contain sodium.

22. A nickel-manganese-aluminum-based composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide; The method includes introducing the obtained lithium nickel-manganese-aluminum-based composite oxide into a solution obtained by mixing an aluminum raw material and an yttrium raw material in an aqueous solvent, mixing the resulting mixture, drying the mixture, and subjecting the mixture to a second heat treatment to obtain a positive electrode active material; The nickel-manganese-aluminum composite hydroxide has a nickel content of 60 mol % or more relative to 100 mol % of the total metals; The content of aluminum in the aluminum raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The method for producing a positive electrode active material, wherein the content of yttrium in the yttrium raw material is 0.05 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.

23. The aluminum content in the aluminum raw material is 0.5 mol % to 1.5 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The method for producing a positive electrode active material according to claim 22, wherein the yttrium content in the yttrium raw material is 0.1 mol % to 0.8 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.

24. the aluminum source comprises aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof; 23. The method of claim 22, wherein the yttrium source comprises yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof.

25. The method for producing a positive electrode active material according to claim 22, wherein the solution in which the aluminum raw material and the yttrium raw material are mixed in the aqueous solvent has a pH of 1.5 to 3.

5.

26. The first heat treatment is carried out at 750°C to 950°C, The method for producing a positive electrode active material according to claim 22, wherein the second heat treatment is performed at 700°C to 850°C.

27. The nickel-manganese-aluminum-based composite hydroxide has a nickel content of 60 mol% to 80 mol% and an aluminum content of 1 mol% to 3 mol% relative to 100 mol% of the total metals. The method for producing a positive electrode active material according to claim 22.

28. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 21.

29. The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 30. The positive electrode of claim 28, wherein

30. 29. The positive electrode of claim 28, wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

31. 29. The positive electrode of claim 28 . a negative electrode, and A lithium secondary battery comprising an electrolyte.

32. 32. The lithium secondary battery according to claim 31, having a charging voltage of 4.45 V or higher.

Citation Information

Patent Citations

  • Cathode activator for nonaqueous lithium secondary battery, manufacturing method of the same, and nonaqueous lithium secondary battery using the cathode activator

    JP2005310744A

  • Nickel-manganese lithium oxide composite material, its manufacturing method, and lithium-ion battery

    JP2022544326A

  • Composite cathode material for lithium-ion batteries, method for preparing same and use thereof

    JP2023500040A

  • Cobalt-free positive electrode material for lithium-ion batteries, manufacturing method thereof, and lithium-ion batteries

    JP2023506527A

  • Positive electrode active material for lithium-ion secondary cell

    WO2013154142A1